FRONT DOOR NEUROLOGY: THE GP EXPERIENCE. Issue 11 (14th October 2015) - Binks, Sophie; Green, Liz
Abstract : Introduction: Neurological symptoms are common in primary care and may represent 10% of consultations. With fewer neurologists in the UK compared to other European nations, the RCGP encourages GP engagement with neurological disease. This project sought to delineate neurological presentations to a large Brighton GP practice. Method: During a four-month GP placement, an FY2 doctor recorded details of patients presenting with neurological symptoms. In tandem, six months of neurology referrals by the permanent GPs were analysed. Results: Common symptoms among 29 FY2 neurologically-oriented appointments included headache (n=8), paraesthesiae (n=4) and funny turns (n=3). Significant new diagnoses included right LACS, post-concussion syndrome and cervical radiculopathy. Most (65%) of patients were managed in GP. Those referred included two to TIA clinic, one to A&E and one to headache service. Of 12 GP referrals reviewed, no neurological examination was documented in 25%, and six provisional diagnoses were in agreement with neurological opinion. After neurology outpatient review, two patients were assessed as having no neurological problem. Conclusions: Headache forms a large component of primary care neurology, but a variety of cases is seen. Acute presentations may be referred to TIA clinic or A&E. Where stated, GP opinion was frequently in line with neurology review.